2017
DOI: 10.1186/s12967-017-1253-1
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human fetal pancreatic progenitor cells ameliorates renal injury in streptozotocin-induced diabetic nephropathy

Abstract: BackgroundDiabetic nephropathy (DN) is a severe complication of diabetes mellitus (DM). Pancreas or islet transplantation has been reported to prevent the development of DN lesions and ameliorate or reverse existing glomerular lesions in animal models. Shortage of pancreas donor is a severe problem. Islets derived from stem cells may offer a potential solution to this problem.ObjectiveTo evaluate the effect of stem cell-derived islet transplantation on DN in a rat model of streptozotocin-induced DM.MethodsPanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Although some reports have shown that several drugs slow the progression of DN, it is difficult to repair a damaged kidney. In recent years, many studies have demonstrated that stem cell transplantation is effective and safe for slowing the development of DN via the regeneration of glomerular tissue [4, 16]. However, transplanted stem cells seem to remain in an oxidative environment, and oxidative stress induces apoptosis and cell cycle arrest, which reduce transplantation efficiency [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some reports have shown that several drugs slow the progression of DN, it is difficult to repair a damaged kidney. In recent years, many studies have demonstrated that stem cell transplantation is effective and safe for slowing the development of DN via the regeneration of glomerular tissue [4, 16]. However, transplanted stem cells seem to remain in an oxidative environment, and oxidative stress induces apoptosis and cell cycle arrest, which reduce transplantation efficiency [37].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the molecular mechanisms underlying DN development are still unclear, and thus, no effective drugs are available to control DN. Recently, stem cell transplantation-based therapy has emerged as a novel therapeutic strategy for DN [4, 5]. This regenerative medicine offers a new method for replenishing damaged cells and promoting the recovery of renal function via differentiation into glomeruli or the activation of paracrine cytokine signaling [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…AGEs have also been implicated in destabilizing PDX‐1 protein, a critical factor for β‐cell survival, thereby impairing insulin synthesis . Recent breakthroughs in the transplantation of human fetal pancreatic progenitor cells have shown promise in preventing RAGE upregulation in the kidney, protecting against diabetic nephropathy . While these advancements are encouraging, more work is needed to fully determine how RAGE and its ligands influence pancreatic β‐cell fate, and how modulation of ligand production, engagement of the ligand with the RAGE receptor, RAGE receptor, and DIAPH1‐dependent intracellular processes may be harnessed to prevent β‐cell dysfunction, diabetes induction, and subsequent pathological consequences.…”
Section: The Receptor For Advanced Glycation Endproducts (Rage) and Imentioning
confidence: 99%
“…[8][9][10][11][12] Diabetic kidney disease occurs in patients with T2DM as a consequence of reduced kidney function, triggered by hypertensive nephrosclerosis and unresolved acute renal failure as the main culminating reasons. [13][14][15][16][17][18][19] Diabetic nephropathy is a diagnosis that refers to specific pathologic structural and functional changes seen in kidneys of patients with T2DM. These changes result in a clinical presentation that is characterized by proteinuria, hypertension, and progressive reductions in kidney function.…”
Section: Introductionmentioning
confidence: 99%